(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To compare selected clinical, endoscopic, and radiological characteristics between congenital and acquired cholesteatoma in pediatric middle ear disease. Methods: A descriptive study using a case series design (both prospective and retrospective) was conducted on 65 patients at the National Otorhinolaryngology Hospital of Vietnam, research period from 2020-2025. Research results: The proportion of male patients was higher than females in both congenital and acquired cholesteatoma groups. The mean age at diagnosis was lower in the congenital group (5.15 ± 3.28 years) compared with the acquired group (9.0 ± 3.74 years). Most congenital cholesteatomas were detected incidentally (78.7%), whereas acquired cholesteatomas commonly presented with otologic symptoms, including otorrhea (59.3%) and otalgia or hearing loss (25%). Endoscopic findings showed that congenital cholesteatomas were predominantly located in the anterosuperior quadrant of the tympanic membrane (54.6%), while acquired cholesteatomas frequently manifested as retraction pockets, tympanic membrane perforations, or attic polyps (81.2%). Regarding mastoid pneumatization, the congenital group mainly exhibited MC2 (39.4%) and MC3 (54.5%) patterns, which were more favorable compared with the acquired group, in which MC1 (53.2%) and MC0 (6.1%) predominated. On computed tomography (HRCT), intact ossicular chains were observed in 51.5% of congenital cholesteatoma cases and 18.7% of acquired cases. Erosion of all three ossicles was identified in 6.1% of the congenital group and 31.3% of the acquired group. Congenital cholesteatomas were primarily confined to the tympanic cavity (69.7%) with limited extension, whereas acquired cholesteatomas were more extensive, frequently associated with mastoid opacification (65.6%), scutum erosion (12.5%), and lateral attic wall destruction (53.1%). Conclusion: Pediatric cholesteatoma may progress insidiously with minimal clinical symptoms despite significant structural changes in the middle ear. Therefore, early recognition of suspicious signs and regular otoscopic follow-up, particularly in male children, those with unilateral recurrent otitis media, or risk factors for Eustachian tube dysfunction, play a crucial role in early diagnosis and timely management.